Rancang Bangun Game Edukasi Berbasis Android Pembantu Sistem Kegiatan Belajar Mengajar (KBM) Mata Pelajaran Komputer Untuk Sekolah - Teuku Muhammad Fawa'ati; Tito Budi Raharto (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2021)
Abstract In the activities of Computer subjects especially the material "Computer Hardware and Software" subject teachers are less than optimal in utilizing and empowering learning resources. Students are less able to develop themselves and tend to be forced to memorize or remember the material presented. The ability of students who are still low in identifying the types and functions of computer hardware, the habit of playing games after school, so that learning outcomes in computer subjects the material "Knowing Computer Hardware and Software" has not been satisfactory. The system development method uses the System Development Life Cycle (SDLC) method and the system design uses UML. The implementation of this system uses Construct 2, as well as system testing using the Black Box. The results achieved are Android-based Educational Game applications to facilitate students in understanding the learning process at school. Keywords  Game, System Development Life Cycle, UML.